Clinical presentation and assessment of older patients presenting with headache to emergency departments: A multicentre observational study. (27th September 2021) - Beck, Sierra; Kinnear, Frances B.; Maree Kelly, Anne; Chu, Kevin H; Sen Kuan, Win; Keijzers, Gerben; Body, Richard; Karamercan, Mehmet A.; Klim, Sharon; Wijeratne, Tissa; Kamona, Sinan; Graham, Colin A; et al.
Abstract: Objective: To describe the characteristics, assessment and management of older emergency department (ED) patients with non‐traumatic headache. Methods: Planned sub‐study of a prospective, multicentre, international, observational study, which included adult patients presenting to ED with non‐traumatic headache. Patients aged ≥75 years were compared to those aged <75 years. Outcomes of interest were epidemiology, investigations, serious headache diagnosis and outcome. Results: A total of 298 patients (7%) in the parent study were aged ≥75 years. Older patients were less likely to report severe headache pain or subjective fever (both P < 0.001 ). On examination, older patients were more likely to be confused, have lower Glasgow Coma Scores and to have new neurological deficits (all P < 0.001). Serious secondary headache disorder (composite of headache due to subarachnoid haemorrhage (SAH), intracranial haemorrhage, meningitis, encephalitis, cerebral abscess, neoplasm, hydrocephalus, vascular dissection, stroke, hypertensive crisis, temporal arteritis, idiopathic intracranial hypertension or ventriculoperitoneal shunt complications) was diagnosed in 18% of older patients compared to 6% of younger patients ( P < 0.001). Computed tomography brain imaging was performed in 66% of patients ≥75 years compared to 35% of younger patients ( P < 0.001). Older patients were less likely to be discharged (43% vs 63%, P < 0.001). Conclusions: Older patients with headache had different clinical features to the younger cohort and were more likely to have a serious secondary cause of headache than younger adults. There should be a low threshold for investigation in older patients attending ED with non‐traumatic headache.